An undiagnosed case of longitudinal vaginal septum in a term woman with obstructed labour: a case report - Kumar, Naina; Tayade, Surekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Congenital anomalies of the female genital tract are often asymptomatic and therefore unrecognized. Longitudinal vaginal septum is a rare Müllerian malformation that may be associated with dyspareunia, dysmenorrhea, primary amenorrhea, and infertility. In this report, the authors present a case of longitudinal vaginal septum in a term primigravida patient with obstructed labour whose diagnosis was only made during labor following bidigital vaginal and speculum examination. After all necessary investigations she was immediately shifted for emergency cesarean section. Patient was discharged under satisfactory condition with healthy baby.